A relação com o saber e o uso de mídias durante o ensino remoto: o que pensam os licenciandos e licenciados da UFSCar campus São Carlos - Fernandes, Ana Júlia (Universidade Federal de São Carlos, 2023)
The Covid-19 pandemic in 2020 and the consequent social isolation brought changes to the whole world and changes and adaptations in the teaching process were necessary, causing the emergency remote teaching to be implemented to give continuity to the undergraduate courses at universities. Based on this, this study sought to understand the relationship undergraduate students of the UFSCar São Carlos campus during the periods of remote emergency education. The research methodology was carried out through the application of an online questionnaire developed in the Google Forms platform, containing, besides the participants' profile, three different sessions with objective, dissertative and Likert scale questions. In total, 35 students from 7 of the 11 undergraduate courses at the University participated in the research, and the analysis of the answers was done by textual discourse analysis. In general, we were able to observe changes in the students' relationship with knowledge in the identity, epistemological and mainly social aspects, and the dimensions of the relationship with knowledge also suffered changes: for some students there was a reduction or even no sense in studying, while for others the sense was enhanced by the use of digital media; the mobilization was also affected since the students pointed out a more active participation, besides the development of autonomy in the learning process, but a smaller portion pointed out a lower mobilization due to procrastination and tiredness. Finally, the activity was influenced in a positive way, in which the students scored it as easier to study with the use of media, or in a negative way, in which the students felt it was more difficult to study in remote learning. Furthermore, some aspects about ENPE were also identified, such as the reproduction of a unilateral traditional teaching due to the teachers' lack of preparation, besides the limitations of format and content of the digital media used. Therefore, this work contributes to the understanding of the teaching-learning process that occurred during the pandemic period and indicates possibilities for future research on the subject.
The relationship with knowledge and the use of media during remote teaching: what graduates of UFSCar campus São Carlos think
Keywords: Relação com o saber; Ensino remoto; Mídias digitais; Licenciatura; UFSCar; Relationship with knowledge; Remote learning; Digital media; Graduation; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM